2020
DOI: 10.1002/zamm.201900274
|View full text |Cite
|
Sign up to set email alerts
|

Integral equation technique for water wave interaction by an array of vertical flexible porous wave barriers

Abstract: Scattering of obliquely incident surface gravity waves by an array of partial flexible vertical porous wave barriers of varied configurations is studied in finite water depth and deep water cases. For the mathematical modeling purpose, linearized water wave theory is considered. Firstly, the problem associated with double vertical barriers is handled for a solution. To solve the problem, the associated BVP (boundary value problem) is transformed into a system of Fredholm integral equations of the second kind. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Kaligatla et al (2017) found that the existence of the porous wall is beneficial for mitigation of the wave loads on the seawall. Koley and Sahoo (2021) investigated water wave interaction with an array of vertical flexible porous barriers. Occurrences of Bragg resonance and cloaking of the multiple barriers were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Kaligatla et al (2017) found that the existence of the porous wall is beneficial for mitigation of the wave loads on the seawall. Koley and Sahoo (2021) investigated water wave interaction with an array of vertical flexible porous barriers. Occurrences of Bragg resonance and cloaking of the multiple barriers were analyzed.…”
Section: Introductionmentioning
confidence: 99%